Encyclopaedia of women health and empowerment - 7 Early midlife and women's health Burdens, pre-menopausal problems and wellness - Kumar, Meenal; Ganguly, N. K.; Kumar, R. (New Delhi Deep & Deep Publications, 2009)
Burdens on health in early midlife